Strategi Peningkatan Mutu Pendidikan dalam Perspektif Manajemen Berbasis Sekolah di SMP Negeri 5 Denpasar - Puspita Utami, A.A.I.A. Chandra; Winaya, I Ketut; Prabawati, Ni Putu Anik (CITIZEN CHARTER; Vol 1 No 01 (2021): Administrasi Publik 2021, 2021)
Indonesia has the problem about the low quality of education at every level in the education unit so that, the government issued Undang-Undang No.20 / 2003. School-based management is a form of management autonomy within the education unit. The background of the problem is how to improve the quality of education in the perspective of school-based management. The theory used in this study is Strategic Management according to Fred R. David, namely strategy formulation, strategy implementation, and strategy evaluation. This research uses descriptive qualitative and the technique of determining the informants is included in the purposive sampling technique. This study found that the quality of education at SMP Negeri 5 Denpasar was quite good in the academic and non-academic fields with the Education Quality Improvement Strategy in School-Based Management Perspective at SMP Negeri 5 Denpasar being implemented by the school in order to get a good quality education. Keywords: Strategic Management, School-based Management.